2014 Global hunger index: The challenge of hidden hunger - von Grebmer, Klaus; Saltzman, Amy; Birol, Ekin; Wiesmann, Doris; Prasai, Nilam; Yin, Sandra; Yohannes, Yisehac; Menon, Purnima; Thompson, Jennifer; Sonntag, Andrea (Welthungerhilfe, 2014)
With one more year before the 2015 deadline for achieving the Millennium Development Goals, the 2014 Global Hunger Index report offers a multifaceted overview of global hunger that brings new insights to the global debate on where to focus efforts in the fight against hunger and malnutrition. The state of hunger in developing countries as a group has improved since 1990, falling by 39 percent, according to the 2014 GHI. Despite progress made, the level of hunger in the world is still “serious,” with 805 million people continuing to go hungry, according to estimates by the Food and Agriculture Organization of the United Nations.